Safety and efficacy of riluzole in spinocerebellar ataxia type 2 in France (ATRIL): a multicentre, randomised, double-blind, placebo-controlled trial. Issue 3 (March 2022) - Coarelli, Giulia; Heinzmann, Anna; Ewenczyk, Claire; Fischer, Clara; Chupin, Marie; Monin, Marie-Lorraine; Hurmic, Hortense; Calvas, Fabienne; Calvas, Patrick; Goizet, Cyril; Thobois, Stéphane; Anheim, Mathieu; et al.
Summary: Background: Riluzole has been reported to be beneficial in patients with cerebellar ataxia; however, effectiveness in individual subtypes of disease is unclear due to heterogeneity in participants' causes and stages of disease. Our aim was to test riluzole in a single genetic disease, spinocerebellar ataxia type 2. Methods: We did a randomised, double-blind, placebo-controlled, multicentre trial (the ATRIL study) at eight national reference centres for rare diseases in France that were part of the Neurogene National Reference Centre for Rare Diseases. Participants were patients with spinocerebellar ataxia type 2 with an age at disease onset of up to 50 years and a scale for the assessment and rating of ataxia (SARA) score of at least 5 and up to 26. Patients were randomly assigned centrally (1:1) to receive either riluzole 50 mg orally or placebo twice per day for 12 months. Two visits, at baseline and at 12 months, included clinical measures and 3T brain MRI. The primary endpoint was the proportion of patients whose SARA score improved by at least 1 point. Analyses were done in the intention-to-treat population (all participants who were randomly assigned) and were done with only the observed data (complete case analysis). This trial is registered at ClinicalTrials.gov (NCT03347344 ) and has been completed. Findings: Between Jan 18, 2018, and June 14, 2019, we enrolled 45 patients. 22 patients were randomly assigned to receive riluzole and 23 to receive placebo. Median age was 42 years (IQR 36–57) in the riluzole group and 49 years (40–56) in the placebo group and 23 (51%) participants were women. All participants presented with moderate-stage disease, characterised by a median SARA score of 13·5 (IQR 9·5–16·5). The primary endpoint, SARA score improvement of at least 1 point after 12 months, was observed in seven patients (32%) in the treated group versus nine patients (39%) in the placebo group, with a mean difference of −10·3% (95% CI −37·4% to 19·2%; p=0·75). SARA score showed a median increase (ie, worsening) of 0·5 points (IQR −1·5 to 1·5) in the riluzole group versus 0·3 points (−1·0 to 2·5) in the placebo group (p=0·70). No serious adverse event was reported in the riluzole-treated group whereas four patients in placebo group had a serious adverse event (hepatic enzyme increase, fracture of external malleolus, rectorrhagia, and depression). The number of patients with adverse events was similar in both groups (riluzole 16 [73%] patients vs placebo 19 [83%] patients; p=0·49). Interpretation: We were able to recruit 45 patients moderately affected by spinocerebellar ataxia type 2 for this trial. Riluzole did not improve clinical or radiological outcomes in these patients. However, our findings provide data on progression of spinocerebellar ataxia type 2 that might prove to be valuable for the design of other clinical trials. Funding: French Ministry of Health.